Freud's Mahabarata - Hiltebeitel, Alf 1942-2023 (Oxford University Press, 2018)
"This book presents several new ways that Freud's work enlivens interpretation of the whole Mahabharata and its vernacular retellings. It takes Freud's 'The 'Uncanny'' as an entrée. Drawing on work of the French psychoanalyst André Green, it shows how the epic's main story from beginning to end follows the 'depressive posture' of the 'dead mother complex.' And it pursues Freud's point in Moses and Monotheism that religious traditions should be studied from what has shaped their past unconsciously, including repressed trauma that affects historical memory. It builds on this premise to offer a new theory of the Mahabharata that focuses on its central background myth, called 'the unburdening of the Earth'"...